Isolasi dan Identifikasi Morfologi serta Biokimia Khamir Hasil Isolasi dari Buah Tomat (Lycopersicum esculentum) yang Berpotensi menghasilkan Bioetanol - Anggrayeni, Yesti Tri; Wijanarka, W; Kusdiyantini, Endang (Bioma : Berkala Ilmiah Biologi, 2019)
Bioethanol can be obtained from the fermentation process by using microorganisms such as yeast. One of the factors that affect height low bioethanol is a kind of yeast, and therefore the isolation and identification of yeast need to be done in order to obtain isolates potentially producing bioetanol. Yeast can be found in various environments, especially rich sugar substrate. Yeast usually living in fruits like tomatoes. This research aims to isolation and identifies yeast from tomatoes and the growth of yeast isolates at 50% glucose concentration test. The method of isolation was performed by streak method with the four scratch quadrant technique on YGP solid media. Identification of macroscopic and microscopic morphology in colonies and cell of yeast. Biochemical identification of the growth in liquid media, the fermentation of sugars test (glucose, galactose, sucrose, maltose, lactose), as well as the growth of yeast,Â  isolates in 50% glucose medium. Determination of bioethanol content is done by distillation process and the measured weight with a pycnometer. The result from isolation yeast on tomato fruits obtained nine isolates is Y1, Y2, Y3, Y4, Y5, Y6, Y7, Y8, Y9. Based on the identification of the morphology, biochemistry, as well as the growth of yeast isolates testing on 50% glucose concentrations of selected isolates Y2 alleged genus Debaryomyces sp. and is able producing ethanol of 8.7% v/v.